PHOTODYNAMIC THERAPY FOR LUNG CANCER: MAJOR INDICATIONS - Yu. A. Ragulin; V. N. Galkin (Сибирский онкологический журнал)
Lung cancer treatment remains a major challenge for modern oncology. Photodynamic therapy (PDT) has proved to be an effective anti-tumor treatment modality for patients with lung cancer. This paper evaluated results of using PDT for lung cancer patients. The effectiveness of PDT was analyzed and the prospects for the development of the method were presented.